E-destination Pariwisata Kota Ternate - Imam Hizbullah; Arie S.M. Lumenta; Oktavian A. Lantang; Jimmy S. Robot (Universitas Sam Ratulangi, 2014)
Abstract - Tourism is a very promising industry in the midst of regional autonomy that demands every area to develop the potential of the resources the area have.The city of ternate is inseparable from optimization of the resources the city owned, one of said resources is tourism, which is the most potent . The concept of e-destination isof one of applicable utilization information technology in the tourism industry and media promotion of effective and efficient in introducing a broadly tourism potential. . By applying the concept of e-destination, one can provide convenience to visitors in trip planning and decision-making process before and during the stay in the town of Ternate. This research resulted in a design and design of information systems by applying the concept of e-tourism destination for the city of Ternate. Keywords : Decision Support , e-Destination, Tourism, Ternate City. Abstrak - Pariwisata menjadi industri yang sangat menjanjikan di tengah otonomi daerah yang memaksa setiap daerah untuk mengembangkan potensi dari sumberdaya yang di miliki daerah tersebut. Kota ternate sendiri tidak terlepas dari pengoptimalisasi sumberdaya yang di miliki, potensi pariwisata di antaranya menjadi salah satu yang sedang dikembangkan. Konsep e-destination merupakan salah satu pemaanfaatan teknologi informasi di industri pariwisata dan media promosi yang efektif dan efisien dalam memperkenalkan secara luas potensi wisata suatu. . Dengan menerapkan konsep e-Destination depat memberikan kemudahan kepada pengunjung dalam perencanaan perjalanan dan proses pengambilan keputusan sebelum dan selama tinggal di kota ternate. Penelitian ini menghasilkan suatu rancangan dan desain sistem informasi dengan menerapkan konsep e-destination untuk pariwisata kota Ternate. Kata kunci : e-Destination, Kota Ternate, Pariwisata, Pengambilan keputusan.